De-centring social capital: exploring the implications of empirical research for conceptualising Christian faith-based social engagement. Issue 1 (2nd January 2019) - Dunlop, Sarah; Buckingham, Heather
ABSTRACT: The concept of social capital is frequently applied in political and academic discussions about the role of churches and other faith groups in contemporary society. This article draws on findings from empirical research in two London-based megachurches to illustrate ways in which these churches contribute to the formulation of relational networks, both among their congregations and beyond them. However, more significantly, it highlights the limitations of the notion of social capital as a means of understanding the nature and purpose of the social engagement of these churches and—by paying close attention to accounts given by those involved in these activities—seeks to provide an alternative, more nuanced account of the way in which relationships were conceived and developed in these contexts.